MALIGNANT HYPERTHERMIA IN A CHILD AFTER MAGNETIC RESONANCE IMAGING: A CASE REPORT - Almeida,Carlos Gustavo de (2020)
ABSTRACT Objective: To report on a case of malignant hyperthermia in a child after a magnetic resonance imaging of the skull was performed using sevoflurane anesthesia. Case description: A 3-year-old boy admitted to the pediatric intensive care unit after presenting clinical and laboratory findings consistent with unspecified viral meningoencephalitis. While the patient was sedated, a magnetic resonance imaging of the skul was performed using propofol followed by the administration of sevoflurane through a laryngeal mask in order to continue anesthesia. Approximately three hours after the start of the procedure, the patient presented persistent tachycardia, tachypnea, generalized muscular stiffness and hyperthermia. With a diagnostic hypothesis of malignant hyperthermia, dantrolene was then administered, which immediately induced muscle stiffness, tachycardia, tachypnea and reduced body temperature. Comments: Malignant hyperthermia is a rare pharmacogenetic syndrome characterized by a severe hypermetabolic reaction after the administration of halogenated inhalational anesthetics or depolarizing muscle relaxants such as succinylcholine, or both. Although it is a potentially fatal disease, the rapid administration of continued doses dantrolene has drastically reduced the morbidity and mortality of the disease.